Dari Konsumsi ke Kontemplasi: Membangun Gaya Hidup Ekologis di Kalangan Kaum Muda Katolik Kalimantan - Jimmy, Andreas (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
The global ecological crisis, which also affects Kalimantan, calls for a new approach that is integral, spiritual, and contextual. This article explores the integration of the vision of integral ecology in the encyclical Laudato Si’ with the local wisdom values of the Dayak people of Kalimantan in shaping ecological awareness among Catholic youth. Using a qualitative-descriptive approach and contextual hermeneutic method, this study examines the relationship between local spiritual traditions—such as the huma betang philosophy and rituals honoring nature—and theological teachings on the integrity of creation. The findings reveal a profound harmony between Dayak ecological spirituality and Catholic ecological theology. Contextual ecological education—through participatory and cultural dialogue approaches—proves effective in fostering ecological conversion among youth. The article concludes that contextual dialogue between local traditions and Catholic ecological theology not only strengthens ecological praxis but also enriches grounded and transformative faith reflection. The Church is called to be a facilitator of change by integrating local values into its ecological mission in a prophetic and participatory manner.